Exploring Transformation Geometry Content in Native Batik of Kerinci: An Ethnomathematics Study - Pitri, Afnesa; Syarifuddin, Hendra; Rusliah, Nur; Putra, Aan (Edumatika, 2023)
The mathematical content in school mathematics must not be isolated from students known context students so the mathematics learning becomes meaningful. One context that is close to the student environment is a popular cultural context, for example batik crafts. This research aims to explore native batik of Kerinci related to transformation geometry content. The type of research used is ethnography. The instrument used in this research was the researcher himself (human instrument). The data collection techniques used are literature study and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the research show that the motif of native batik of Kerinci contains mathematical concepts in the geometry transformation content, namely reflection, translation, rotation and dilation. These findings can be integrated into mathematics learning through transformation geometry learning tools using the context of native batik of Kerinci.